1999
DOI: 10.1127/archiv-hydrobiol/146/1999/471
|View full text |Cite
|
Sign up to set email alerts
|

Life history patterns of stream-dwelling caddis

Abstract: With 13 figures and 3 tables Abstract: Full life histories of fourteen coexisting species of caddis in an Irish stream are described. The study is based on growth patterns and distribution of larval head capsule width through time. It also notes adult fl ight periods. Most species had simple life histories and were univoltine (Agapetus fuscipes, Hydropsyche sUtalai, H. instabi lis, PhUopotamus montanus, Ecclisopteryx guttulata, Glossosoma conformis, Drusus annulatus, Po tamophylax cingulatus and Halesus radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 0 publications
5
25
0
1
Order By: Relevance
“…in the last instar. H. siltalai, on the other hand, overwinter mainly as the third or fourth instar, and flies later in summer (Hildrew and Edington, 1979;Sangpradub et al, 1999). In 2008, however, sampling was done in early June which does not explain the absence of H. pellucidula and C. lepida in the Kuusaankoski rapids.…”
Section: Tablementioning
confidence: 99%
“…in the last instar. H. siltalai, on the other hand, overwinter mainly as the third or fourth instar, and flies later in summer (Hildrew and Edington, 1979;Sangpradub et al, 1999). In 2008, however, sampling was done in early June which does not explain the absence of H. pellucidula and C. lepida in the Kuusaankoski rapids.…”
Section: Tablementioning
confidence: 99%
“…Recent examples across various time frames include variable duration of pupal development in a geometrid moth (Tammaru et al, 1999), variable egg hatch of a bushcricket (Hockham et al, 2001), variable larval duration in a burnet moth (Wipking and Kuntz, 2000), and alternative routes among directly developing, dormant and mobile forms in a glycyphagid mite (Knülle, 2003). Sangpradub et al (1999) found intraspecific variation in development rates, a wide range of simultaneous size classes, an ability to overwinter in different larval stages, and asynchronous extended flight periods in caddisflies from a temperate stream. Neal et al (1997) interpreted the variable spring egg hatch of Malacosoma (which was independent of spring temperatures) as a means to offset potential losses of young larvae from late winter storms.…”
Section: Risk Spreading and Prolonged Dia-pausementioning
confidence: 99%
“…Firstly, the size of the benthos area sampled was perhaps too coarse to detect the segregation of species into microhabitats of the size inferior to that of cobble (e.g., top vs. bottom of a stone; Hildrew and Edington, 1979). Secondly, perhaps to avoid competition, pupal casebuilding periods can be temporally segregated (at least in parts), which has been reported for co-existing species in the genera Hydropsyche and Rhyacophila (Hildrew and Edington, 1979;Ce´re´ghino et al, 1997;Sangpradub et al, 1999). In combination, these two reasons potentially created so much noise that the signal of an actually existing competition among co-existing RCWs could not be detected.…”
Section: Indicators Of Potential Competition For Grain Resources Amonmentioning
confidence: 99%
“…Confirmed species identifications of larvae are currently often impossible in this species group (Waringer and Graf, 1997), making it difficult to identify prepupae and immature pupae to species. The life cycle of Rhyacophila species is often untypical, as prepupae and pupae can be found spread over many months of the year and the data suggest that their builders use the pupal case for y 2-5 months (Ce´re´ghino et al, 1997;Sangpradub et al, 1999).…”
Section: Data Collection and Analysesmentioning
confidence: 99%